Load type catalyst with low noble metal content as well as preparation method and application of load type catalyst
By using a hierarchical porous all-silica molecular sieve to support a low-content Pt and SnOx-coated Pt alloy structure in a propane dehydrogenation catalyst, the issues of catalyst stability and cost were resolved, and efficient propylene production was achieved.
Patent Information
- Application Number
- CN202410944892.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2026-01-16
AI Technical Summary
Existing propane dehydrogenation catalysts suffer from poor stability, high precious metal content, high cost, and environmental pollution, making it difficult to meet the industrial demand for low-carbon olefin production.
Using a high external specific surface area hierarchical porous all-silica molecular sieve as a support, a low content of Pt component and auxiliary metal component is loaded to form an alloy structure of SnOx coated with Pt, which improves the dispersion and stability of the catalyst.
It achieves high catalytic activity and stability with low precious metal content, increases propylene yield, reduces catalyst cost, and is suitable for large-scale industrial production.
Smart Images

Figure CN121338802A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of alkane dehydrogenation catalysts, specifically relating to a low-noble-metal-content supported catalyst, its preparation method, and its application. Background Technology
[0002] Low-carbon alkane dehydrogenation technology not only improves the rational utilization rate of oil and gas resources, but also produces high-value-added low-carbon olefins, such as propylene, which are essential organic chemical raw materials directly related to the development of the national economy. In recent years, with the increasing demand for propylene, traditional technologies such as catalytic cracking and steam cracking for producing low-carbon olefins can no longer fully meet market demand. Propane direct dehydrogenation to propylene (PDH) technology has become one of the main sources of propylene production capacity due to its short process flow, single product, high propylene yield, and high economic efficiency.
[0003] Currently, over 90% of the world's industrialized propane dehydrogenation technologies originate from UOP's Oleflex process and Lummus's Catofin process in the United States. Catalysts are the core technology for propane dehydrogenation, with typical representatives being Pt-based and Cr-based catalysts. Cr-based catalysts can cause severe environmental pollution during preparation, use, and subsequent recovery, and suffer from poor operational stability, frequent regeneration requirements, and high energy consumption, making them unsuitable for large-scale adoption. Pt-based catalysts, due to their high intrinsic dehydrogenation activity, are the preferred active metal component for PDH technology. However, these catalysts still face several serious problems during industrial operation, such as the tendency for Pt metal particles to agglomerate, sinter, and form carbon deposits at high temperatures, resulting in poor stability. Furthermore, the high price of the precious metal Pt leads to high catalyst costs, and the combination with four continuous moving bed processes results in high investment costs and energy consumption. All these problems hinder the development of the low-carbon olefin production industry. Therefore, it is essential to develop a novel alkane dehydrogenation catalyst that is relatively low-cost, stable, environmentally friendly, and has simple supporting processes. Summary of the Invention
[0004] The purpose of this invention is to overcome the problems of poor stability and high precious metal content in the prior art, and to provide a low-precious-metal-content supported catalyst, its preparation method, and its application. The catalyst of this invention uses a hierarchical porous all-silica molecular sieve with a high external specific surface area as a support, which can effectively improve the dispersion and utilization rate of Pt particles and reduce the amount of precious metals used. Furthermore, under the action of a high content of promoters, an alloy structure of SnOx-coated Pt is formed, which can significantly inhibit the high-temperature migration and agglomeration of the catalyst and improve catalytic stability. When applied to propane dehydrogenation, the catalyst of this invention exhibits characteristics such as low precious metal content, high catalytic activity, high stability, and high propylene yield.
[0005] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:
[0006] A first aspect of the present invention is to provide a low-noble-metal-content supported catalyst, comprising: a molecular sieve support, and a noble metal component and an auxiliary metal component supported on the support, wherein the molecular sieve support is a hierarchical porous all-silica molecular sieve, and the auxiliary metal component includes a first auxiliary metal component and an optional second auxiliary metal component, wherein the catalyst comprises an alloy structure in which the noble metal component is coated with an oxide of the first auxiliary metal component.
[0007] According to the present invention, in the supported catalyst with low noble metal content:
[0008] The multi-level porous all-silica molecular sieve is selected from at least one of MFI type all-silica molecular sieve and MEL type all-silica molecular sieve;
[0009] The noble metal component is Pt;
[0010] The first auxiliary metal component is selected from at least one of Sn, Zn, Ga, and Cu;
[0011] The second auxiliary metal component is selected from at least one of alkali metal elements and alkaline earth metal elements, for example, it can be selected from at least one of Li, Na, K, Rb, Cs, Mg, Ca, and Sr.
[0012] According to the present invention, in the supported catalyst with low noble metal content:
[0013] Based on a total weight of 100 wt% for the supported catalyst with low precious metal content, the content of the precious metal component is 0.1-1 wt%, the content of the first auxiliary metal component is 0.1-15 wt%, and the content of the second auxiliary metal component is 0-2 wt%.
[0014] Preferably, based on a total weight of 100 wt% for the low-precious-metal-content supported catalyst, the content of the precious metal component is 0.1-0.5 wt%, the content of the first auxiliary metal component is 0.1-10 wt%, and the content of the second auxiliary metal component is 0-1 wt%.
[0015] A second aspect of the present invention is to provide a method for preparing a low-noble-metal-content supported catalyst as described in one of the objectives of the present invention, comprising: impregnating the molecular sieve support in a precursor solution containing a noble metal component and an auxiliary metal component, and obtaining the low-noble-metal-content supported catalyst by post-treatment.
[0016] According to the present invention, the preparation method of the low-noble-metal-content supported catalyst specifically includes the following steps:
[0017] (1) Mix silicon source, organic template agent and water evenly to form a mixed gel, then perform hydrothermal crystallization, centrifugation, washing, drying and calcination to obtain all-silicon molecular sieve;
[0018] (2) The all-silicon molecular sieve obtained in step (1) is impregnated in a mixed aqueous solution containing a noble metal compound and a first auxiliary metal compound. Then, the obtained catalyst precursor is optionally impregnated in an aqueous solution containing a second auxiliary metal compound. After solvent removal, drying and calcination, the low noble metal content supported catalyst is obtained.
[0019] According to the present invention, in the preparation method of the low-noble-metal-content supported catalyst:
[0020] The silicon source is selected from at least one of tetraethyl silicate, silica gel, and silica sol, preferably tetraethyl silicate; wherein, the tetraethyl silicate can be a common commercially available product, such as: tetraethyl orthosilicate, tetraethyl orthosilicate, tetraethyl silicate-28, tetraethyl silicate-40, etc.
[0021] The organic template agent is selected from at least one of organic ammonium compounds, preferably from at least one of tetraethylammonium hydroxide, tetraethylammonium bromide, tetrapropylammonium hydroxide, tetrapropylammonium bromide, tetrapropylammonium chloride, tetrapropylammonium fluoride, tetrabutylammonium hydroxide, tetrabutylammonium bromide, and tetrabutylammonium chloride;
[0022] The noble metal compound is selected from at least one of the chlorine-containing compounds and nitrates of Pt, preferably from at least one of chloroplatinic acid, platinum dichloride, platinum tetraamminenitrate, and platinum tetrachloride;
[0023] The first auxiliary metal compound is selected from soluble metal salt compounds of at least one metal selected from Sn, Zn, Ga, and Cu, preferably from chlorides and / or nitrates of at least one metal selected from Sn, Zn, Ga, and Cu; when Sn is used as the auxiliary metal, the Sn source is selected from one or more of crystalline SnCl4·5H2O and SnCl2·2H2O; when Zn or Cu is used as the auxiliary metal, the Zn source is selected from one or more of ZnCl2 and Zn(NO3)2·6H2O; the Cu source is selected from one or more of CuCl4, CuCl2·2H2O, and Cu(NO3)2·3H2O; when Ga is used as the auxiliary metal, the Ga source is selected from one or more of GaCl3 and Ga(NO3)2·xH2O.
[0024] The second auxiliary metal compound is selected from at least one of alkali metal salts and alkaline earth metal salts, preferably from chlorides and / or nitrates of at least one of alkali metals and alkaline earth metals.
[0025] According to an embodiment of the present invention, the water used is preferably water that has undergone electrolyte removal treatment, for example, deionized water.
[0026] According to the present invention, in step (1) of the preparation method of the low-noble-metal-content supported catalyst:
[0027] The molar ratio of the silicon source, organic template agent and water is 1:(0.1-1.0):(10-100), preferably 1:(0.1-0.5):(10-80), wherein the silicon source is based on its SiO2 content;
[0028] The mixing conditions in step (1) can be selected within a wide range. For example, the stirring conditions are: stirring temperature 20-40℃ and stirring time 2-12h.
[0029] The conditions for hydrothermal crystallization are: temperature 120-180℃ and time 24-120h; in step (1), crystallization can be carried out at a low temperature first, and the conditions for low temperature crystallization are: crystallization temperature 50-120℃ and crystallization time 24-120h.
[0030] There are no special limitations on centrifugation in step (1). Common centrifugation equipment and operating conditions can be used. For example, the centrifugation conditions are: speed of 3000 to 5000 rpm and time of 0.5 to 2 hours. After centrifugation, wash with deionized water until the pH value is between 7 and 8.
[0031] There are no special restrictions on drying in step (1). Common drying equipment and drying conditions can be used. For example, the drying conditions are: temperature 80-120℃ and time 6-12h.
[0032] In step (1), the roasting can be carried out using common drying equipment and drying conditions. For example, the roasting conditions are: heating to 500-600℃ at a heating rate of 1-2℃ / min and roasting time of 4-6h; preferably roasting at 550-580℃.
[0033] According to the present invention, in the preparation method of the low precious metal content supported catalyst, the all-silica molecular sieve obtained in step (1) has a hierarchical pore structure and is at least one of MFI type all-silica molecular sieve and MEL type all-silica molecular sieve.
[0034] Preferably, the particle size of the all-silica molecular sieve is 50–600 nm;
[0035] Preferably, the external specific surface area of the all-silica molecular sieve is 150–450 m². 2 / g, preferably 300-420m 2 / g;
[0036] Preferably, the mesopore volume of the all-silica molecular sieve is 0.5–1.5 cm³. 3 / g, preferably 0.8~1.2cm 3 / g.
[0037] According to the present invention, in step (2) of the preparation method of the low-noble-metal-content supported catalyst,
[0038] In step (2), the solvent in the mixed aqueous solution of the metal compound is deionized water. The amount of deionized water is not particularly limited and can be selected within a wide range. For example, the amount of deionized water is more than 5 times the mass of the metal compound.
[0039] The impregnation can be carried out using common impregnation methods, and the impregnation conditions can be selected within a wide range. For example, the impregnation conditions are: temperature 20-60℃ and time 4-12h.
[0040] The solvent removal is performed by rotary evaporation. Preferably, the rotary evaporation conditions are: temperature 70-80°C, rotation speed 120-150 rpm, and vacuum degree 65-75 mbar.
[0041] The drying conditions are: temperature 80–120°C, time 6–12 hours;
[0042] The calcination conditions are as follows: heating to 500-600°C at a heating rate of 1-2°C / min, and calcination time of 4-6 hours; preferably calcination is carried out at 550-580°C.
[0043] A third aspect of the present invention is to provide the application of the low-noble-metal-content supported catalyst of the first aspect of the present invention or the low-noble-metal-content supported catalyst obtained by the preparation method of the second aspect of the present invention in the propane dehydrogenation reaction, preferably in the propane dehydrogenation reaction to prepare propylene.
[0044] Specifically, the application includes: contacting propane with the low-noble-metal-content supported catalyst and carrying out a propane dehydrogenation reaction to obtain propylene under a hydrogen atmosphere; specifically, after the catalyst is crushed into particles by pressing, a certain mass of catalyst is weighed and loaded into a reactor, the upper and lower beds are fixed with quartz sand, the reaction gas is diluted with H2, and a dehydrogenation reaction is carried out to obtain propylene.
[0045] Preferably, in the dehydrogenation reaction, the propane gas mass hourly space velocity is 1–50 h⁻¹. -1 The feed pressure ratio of H2 to propane is 1:(1~8), and the dehydrogenation reaction temperature is 550~620℃.
[0046] Compared with the prior art, the beneficial effects of the present invention are:
[0047] (1) The all-silica molecular sieve supported catalyst provided by the present invention can provide a higher external specific surface area, improve the dispersion of active components, and improve catalytic activity.
[0048] (2) The catalyst provided by this invention uses a low content of precious metal Pt, which is relatively inexpensive, environmentally friendly and efficient. When the mass percentage of Pt is as low as about 0.1 wt%, the alloy structure of high content of additives coated with Pt can significantly inhibit the high-temperature migration and agglomeration of Pt particles, and obtain ultra-high dehydrogenation catalytic activity and stability. The average propylene yield within 12 hours of reaction is 4 times that under the same conditions with a high content of 0.5 wt% Pt.
[0049] (3) The catalyst of the present invention has low Pt content and high utilization rate. The target catalyst can be obtained by simple impregnation and calcination. The operation is simple and easy to repeat, and the preparation cost is low. Compared with the existing industrial PtSn-based catalyst (Pt content 0.5wt%), it is cheaper and suitable for large-scale industrial production. Attached Figure Description
[0050] Figure 1 The image shows the X-ray diffraction (XRD) pattern of the all-silica molecular sieve supported catalyst prepared in Example 1; wherein the reference molecular sieve is the commercially available Silicalite-1 molecular sieve.
[0051] Figure 2 The N2- physical adsorption-desorption curves of the all-silica molecular sieve supported catalyst prepared in Example 1 are shown.
[0052] Figure 3 The image shows a scanning electron microscope (SEM) image of the all-silica molecular sieve supported catalyst prepared in Example 1.
[0053] Figure 4 The image shows a transmission electron microscope (TEM) image of the all-silica molecular sieve supported catalyst prepared in Example 1.
[0054] Figure 5 Transmission electron microscopy (TEM) image of the all-silica molecular sieve supported catalyst prepared in Comparative Example 1. Detailed Implementation
[0055] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0056] The specific embodiments of the present invention will be explained and described below. It should be understood that the following description of the specific embodiments is only for explaining and illustrating the present invention, and is not intended to limit the present invention.
[0057] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0058] Example 1:
[0059] 30.85 g of tetraethyl orthosilicate (TEOS) was slowly added dropwise to 32.82 g of tetrapropylammonium hydroxide (TPAOH) aqueous solution (TPAOH concentration 25 wt%). The mixture was sealed and stirred overnight at room temperature to allow complete hydrolysis of the tetraethyl orthosilicate. The resulting gel solution was transferred to a hydrothermal reactor and crystallized at 170 °C for 48 h. After cooling to room temperature, the crystallized product was centrifuged at high speed and washed with deionized water until pH = 7.5. It was then dried overnight at 120 °C in an oven. Finally, the temperature was increased to 580 °C at a rate of 2 °C / min and calcined at 580 °C for 6 h to obtain spherical nano-Silicalite-1 molecular sieves.
[0060] 0.0261 g of chloroplatinic acid hexahydrate and 0.2645 g of crystalline tin tetrachloride were weighed and dissolved in 2 g of deionized water. The solutions were stirred until completely dissolved to obtain an aqueous solution of the metal precursor. Preparation of the supported catalyst: The nano-Silicalite-1 molecular sieve prepared above was impregnated into the aqueous solution of the metal precursor. After impregnation at room temperature overnight, the impregnated sample was desolventized by vacuum evaporation (72 mbar) at 70°C water bath and 120 rpm. It was then dried in a 100°C drying oven for 8 h, and finally calcined in a muffle furnace at 580°C for 6 h to obtain the supported catalyst, denoted as catalyst A1. The mass percentages of each metal component, based on the total mass of the catalyst, were Pt: 0.1 wt% and Sn: 1.0 wt%.
[0061] The phase structure characterization results of catalyst A1 are shown in the figure. Figure 1 As shown in the figure, the catalyst has a high degree of crystallinity, exhibiting significant MEL structural characteristic peaks, with a relative crystallinity of 95%. Figure 2 The N2- physical adsorption-desorption results showed that the catalyst exhibits a hierarchical porous structure with an external specific surface area as high as 379 cm². 2 / g, combined Figure 3 SEM results showed that the catalyst grain size was 50–100 nm, and this smaller grain size contributed to the dispersion of metal nanoparticles on the catalyst surface. Figure 4The TEM results show that in the calcined sample, ultra-low Pt content forms SnO under the action of high Sn content additive. x The Pt-coated alloy structure will significantly inhibit the high-temperature migration and agglomeration of active Pt, which will help improve the stability of the catalyst.
[0062] Example 2:
[0063] The catalyst preparation method was the same as in Example 1. The difference was that, based on the impregnation of Pt and Sn components, a stepwise impregnation method was used to further load an alkali metal K promoter. 0.1689 g of KCl was dissolved in 2 g of deionized water and impregnated onto the prepared catalyst precursor containing Pt and Sn metal components. Similarly, the impregnated sample was vacuumed (72 mbar) in a rotary evaporator at 70°C and 120 rpm to remove the solvent, then dried in a 100°C drying oven for 8 h, and finally calcined in a muffle furnace at 580°C for 6 h to obtain catalyst A2. The mass percentages of each metal component, based on the total mass of the catalyst, were Pt: 0.1 wt%, Sn: 1.0 wt%, and K: 1.0 wt%.
[0064] Example 3:
[0065] The catalyst preparation method was the same as in Example 1. The difference lay in the impregnation content of the metal precursor solution: 0.0651 g of chloroplatinic acid hexahydrate and 0.2645 g of crystalline tin tetrachloride were weighed, dissolved in 2 g of deionized water, impregnated with the prepared molecular sieve overnight, and then the solvent was removed, dried, and calcined to obtain the corresponding catalyst, denoted as catalyst A3. The metal content was determined using inductively coupled plasma atomic emission spectrometry. Based on the total mass of the catalyst, the mass percentages of each metal component were Pt: 0.25 wt% and Sn: 1.0 wt%.
[0066] Example 4:
[0067] The catalyst preparation method was the same as in Example 1. The difference was that Cu was chosen as the promoter. 0.0261 g of chloroplatinic acid hexahydrate and 3.191 g of copper nitrate trihydrate were dissolved in 2 g of deionized water to prepare a mixed aqueous solution of metal precursors. This solution was mixed with the molecular sieve prepared above, impregnated overnight, and then subjected to the same desolventizing, drying, and calcining steps to obtain a catalyst supported on PtCu components, denoted as catalyst A4. The metal content was determined using inductively coupled plasma atomic emission spectrometry (ICP-AES). Based on the total mass of the catalyst, the mass percentages of each metal component were Pt: 0.1 wt% and Cu: 9.5 wt%.
[0068] Example 5:
[0069] 41.79 g of tetrabutylammonium hydroxide (TPAOH) aqueous solution (TPAOH concentration 25 wt%) was weighed and mixed with 30.80 g of deionized water. Then, 27.41 g of tetraethyl orthosilicate (TEOS) was slowly added dropwise to the mixture. The mixture was sealed and stirred overnight at room temperature to allow complete hydrolysis of the tetraethyl orthosilicate. The resulting gel solution was transferred to a hydrothermal reactor and crystallized at 110 °C for 48 h. The temperature was then directly increased to 170 °C for 36 h. After cooling to room temperature, the crystallized product was centrifuged at high speed and washed with deionized water until pH = 7.5. It was then dried overnight at 120 °C in an oven. Finally, the temperature was increased to 580 °C at a rate of 2 °C / min and calcined at 580 °C for 6 h to obtain nano-sized Silicalite-2 molecular sieves.
[0070] 0.0231 g of chloroplatinic acid hexahydrate and 0.2350 g of crystalline tin tetrachloride were weighed and dissolved in 2 g of deionized water to prepare a mixed aqueous solution of metal precursors. This solution was then mixed with the molecular sieve prepared above and impregnated overnight. After solvent removal, drying, and calcination (operating conditions were the same as in Example 1), a catalyst supported on PtSn components was obtained, denoted as catalyst A5. The mass percentages of each metal component, based on the total mass of the catalyst, were Pt: 0.1 wt% and Sn: 1.0 wt%.
[0071] Example 6:
[0072] The catalyst preparation method is the same as in Example 5. The difference is that alkaline earth metal Ca is added as a promoter. 0.4665 g of calcium nitrate tetrahydrate is dissolved in 2 g of deionized water and mixed with the metal catalyst precursor supported on Pt and Sn components. The mixture is stirred and impregnated overnight. After the same steps of solvent removal, drying, and calcination, a catalyst supported on Pt, Sn, and Ca components is obtained, denoted as catalyst A6. The mass percentages of each metal component, based on the total mass of the catalyst, are Pt: 0.1 wt%, Sn: 1.0 wt%, and Ca: 1.0 wt%.
[0073] Comparative Example 1:
[0074] The catalyst preparation method is the same as in Example 1, except that 0.1306 g of chloroplatinic acid hexahydrate and 0.2645 g of crystalline tin tetrachloride were weighed and dissolved in 2 g of deionized water, stirred until completely dissolved, to obtain an aqueous solution of the metal precursor. Preparation of the supported catalyst: This was mixed with the molecular sieve prepared above, impregnated overnight, and after solvent removal, drying, and calcination, a catalyst supported on PtSn components was obtained, denoted as catalyst D1. The mass percentages of each metal component, based on the total mass of the catalyst, were Pt: 0.5 wt% and Sn: 1.0 wt%. The corresponding TEM spectrum of this catalyst is shown in [Figure number missing]. Figure 5As shown in the figure, the metal particles did not form an alloy structure of SnOx coating active Pt on the catalyst surface.
[0075] Comparative Example 2:
[0076] 16.80 g of tetrapropylammonium hydroxide (TPAOH) aqueous solution was weighed and mixed with 61.80 g of deionized water. Then, 21.47 g of tetraethyl orthosilicate (TEOS) was slowly added dropwise to the mixture. The mixture was sealed and stirred overnight at room temperature to allow complete hydrolysis of the tetraethyl orthosilicate. The resulting gel solution was transferred to a hydrothermal reactor and crystallized at 170 °C for 72 h. After cooling to room temperature, the crystallized product was centrifuged at high speed and washed with deionized water until pH 7.5. It was then dried in a 100 °C oven for 8 h, and finally heated to 580 °C at a rate of 2 °C / min and calcined at 580 °C for 6 h to obtain hexagonal plate-like Silicalite-1 molecular sieve. 0.0921 g of chloroplatinic acid hexahydrate and 0.1675 g of crystalline tin tetrachloride were dissolved in 2 g of deionized water to prepare a mixed aqueous solution of metal precursors. This solution was then mixed with the molecular sieve prepared above, impregnated overnight, and after solvent removal, drying, and calcination, a catalyst supported on Pt and Sn components was obtained, denoted as catalyst D2. The mass percentages of each metal component, based on the total mass of the catalyst, were Pt: 0.5 wt% and Sn: 1.0 wt%.
[0077] Comparative Example 3:
[0078] Referring to the preparation method of the supported catalyst in Example 1, a conventional impregnation method was used. Equal masses of active metal and auxiliary metal components were weighed and dissolved in deionized water. After thorough mixing, an aqueous solution of the metal precursor (same as in Example 1) was prepared and impregnated onto a commercially available γ-Al₂O₃ support. The impregnated sample was then subjected to vacuum (72 mbar) in a rotary evaporator at 70°C and 120 rpm to remove the solvent. It was then dried in a 100°C drying oven for 8 hours and calcined in a muffle furnace at 580°C for 6 hours to obtain the γ-Al₂O₃ supported catalyst, denoted as catalyst D3. The mass percentages of each metal component, based on the total mass of the catalyst, were Pt: 0.5 wt% and Sn: 1.0 wt%.
[0079] Test Example 1:
[0080] The catalyst prepared in Example 1 was subjected to crystal phase scanning using a Bruker AXS D8 Advance X-ray diffractometer (Germany). See the example below for details. Figure 1 It can be seen that the catalyst has good crystallinity, showing a standard crystal phase with a MEL structure. No diffraction peaks of Pt and Sn metal components were found, indicating that the active components are highly dispersed.
[0081] Test Example 2:
[0082] The N2 physical adsorption-desorption curves of the catalysts prepared in Examples 1-6 and Comparative Examples 1-3 were measured using an Autosorb iQ fully automated adsorption analyzer manufactured by Quanta Computer in the United States. Simultaneously, the specific surface area and pore volume of each catalyst sample in Examples 1-6 and Comparative Examples 1-3 were calculated. Examples are shown below. Figure 2 The results are detailed in Table 1.
[0083] Table 1
[0084]
[0085] In Table 1, S Micro This refers to the specific surface area of the micropores in the synthesis of each catalyst; S Ext This refers to the external specific surface area; S BET This refers to the total specific surface area; V Micro This refers to the micropore volume; V meso This refers to the mesoporous pore volume; V Total This refers to the total pore volume of the catalyst.
[0086] Test Example 3:
[0087] The catalysts in Examples 1-6 were analyzed using a Hitachi S-4800 cold field emission scanning electron microscope. Examples are shown below. Figure 3 .
[0088] Test Example 4:
[0089] The catalyst of this invention was tested and evaluated in a constant-temperature micro fixed-bed reactor under the following conditions: approximately 0.5 g of catalyst was mixed with 10 g of quartz sand in stages and packed into a quartz tube reactor with an inner diameter of Ф = 10 mm. The reaction pressure was atmospheric pressure, the reaction gas was diluted with H2, and the propane gas hourly space velocity was 3 h⁻¹. -1 The feed pressure ratio of H2 to propane was 1:4, and the reaction temperature was 550℃-600℃. The product distribution was analyzed by Agilent 7890A gas chromatograph.
[0090]
[0091] The propane dehydrogenation performance evaluation results of each catalyst in Examples 1-6 and Comparative Examples 1-3 are shown in Table 2. Table 2 shows the corresponding propane conversion and propylene selectivity at the initial stage (10 min of reaction) and after 12 h of reaction. It can be seen that the catalyst exhibits excellent propane conversion and propylene selectivity, with a propylene selectivity as high as 97.5% and an initial propylene formation rate as high as 22.4 mol·g⁻¹. Pt -1 ·h-1 This is four times that of an industrial load of 0.5 wt%, significantly improving the effective utilization rate of Pt. In stark contrast, in Comparative Example D1, the propane conversion rate decreased by nearly 8% under the influence of high Pt content.
[0092] The catalysts obtained in Examples 2-6 were tested and found to have similar catalytic stability to those in Example 1. The catalytic performance of the catalysts obtained in Examples 1-6 and Comparative Examples 1-3 is shown in Table 2.
[0093] Table 2
[0094]
[0095] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
[0096] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.
[0097] All publications, patent applications, patents, and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art. In case of conflict, the definitions in this specification shall prevail.
[0098] When this specification uses the prefixes “known to those skilled in the art,” “prior art,” or similar terms to derive materials, substances, methods, steps, apparatus, or components, the objects derived from such prefixes cover those commonly used in the art at the time of this application, but also include those that are not currently commonly used but will become generally recognized in the art as suitable for similar purposes.
[0099] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values; such ranges or values should be understood to include values close to them. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In principle, various technical solutions can be combined with each other to obtain new technical solutions, which should also be considered as specifically disclosed herein.
[0100] In the context of this specification, except where expressly stated otherwise, any matters or issues not mentioned shall apply directly to those known in the art without any modification.
[0101] Furthermore, any implementation described herein can be freely combined with one or more other implementations described herein, and the resulting technical solutions or technical ideas shall be regarded as part of the original disclosure or original record of the present invention, and should not be regarded as new content not disclosed or anticipated herein, unless those skilled in the art consider the combination to be obviously unreasonable.
Claims
1. A low noble metal content supported catalyst comprising: A molecular sieve carrier, and a noble metal component and an auxiliary metal component supported on the carrier, the molecular sieve carrier being a full-silica molecular sieve with multiple levels of pores, and the auxiliary metal component including a first auxiliary metal component and optionally a second auxiliary metal component, wherein the catalyst contains an alloy structure in which the first auxiliary metal component oxide coats the noble metal component.
2. The low noble metal content supported catalyst according to claim 1, wherein, the full-silica molecular sieve with multiple levels of pores is selected from at least one of MFI type full-silica molecular sieve and MEL type full-silica molecular sieve; and / or, the noble metal component is Pt; and / or, the first auxiliary metal component is selected from at least one of Sn, Zn, Ga and Cu; and / or, the second auxiliary metal component is selected from at least one of alkali metal element and alkaline earth metal element.
3. The low noble metal content supported catalyst according to claim 1 or 2, wherein, the content of the noble metal component is 0.1-1 wt%, the content of the first auxiliary metal component is 0.1-15 wt%, and the content of the second auxiliary metal component is 0-2 wt%, based on the total weight of the low noble metal content supported catalyst being 100 wt%; and preferably, the content of the noble metal component is 0.1-0.5 wt%, the content of the first auxiliary metal component is 0.1-10 wt%, and the content of the second auxiliary metal component is 0-1 wt%, based on the total weight of the low noble metal content supported catalyst being 100 wt%.
4. A process for the preparation of a supported catalyst according to any one of claims 1 to 3, comprising: The molecular sieve carrier is impregnated in a precursor solution containing the noble metal component and the auxiliary metal component, and the low noble metal content supported catalyst is obtained after post-treatment.
5. The preparation method according to claim 4, characterized in that, Specifically comprising the following steps: (1) uniformly mixing a silicon source, an organic template agent and water, hydrothermally crystallizing the mixed gel, centrifugally separating, washing, drying and calcining to obtain the full-silica molecular sieve; (2) impregnating the full-silica molecular sieve obtained in step (1) in a mixed aqueous solution containing a noble metal compound and a first auxiliary metal compound, and then optionally impregnating the obtained catalyst precursor in an aqueous solution containing a second auxiliary metal compound, and then removing solvent, drying and calcining to obtain the low noble metal content supported catalyst.
6. The preparation method according to claim 5, wherein, the silicon source is selected from at least one of tetraethyl orthosilicate, silica gel and silica sol, and is preferably tetraethyl orthosilicate; and / or, the organic template agent is selected from at least one of organic ammonium compounds, and is preferably selected from at least one of tetraethylammonium hydroxide, tetraethylammonium bromide, tetrapropylammonium hydroxide, tetrapropylammonium bromide, tetrapropylammonium chloride, tetrapropylammonium fluoride, tetrabutylammonium hydroxide, tetrabutylammonium bromide and tetrabutylammonium chloride; and / or, the noble metal compound is selected from at least one of chlorine-containing compounds and nitrate of Pt, and is preferably selected from at least one of chloroplatinic acid, platinum dichloride, tetraammine platinum nitrate and platinum tetrachloride; and / or, The first auxiliary metal compound is selected from at least one metal of Sn, Zn, Ga, Cu, preferably at least one metal of Sn, Zn, Ga, Cu of chloride and / or nitrate; and / or, The second auxiliary metal compound is selected from at least one of alkali metal salt, alkaline earth metal salt, preferably at least one metal of alkali metal, alkaline earth metal of chloride and / or nitrate.
7. The preparation method according to claim 5, characterized in that, In the step (1), the molar ratio of the silicon source, the organic template agent and water is 1: (0.1-1.0): (10-100), preferably 1: (0.1-0.5): (10-80), wherein the silicon source is calculated based on SiO2 contained therein; and / or, The stirring condition is that the stirring temperature is 20-40℃ and the stirring time is 2-12h; and / or, The hydrothermal crystallization condition is that the temperature is 120-180℃ and the time is 24-120h; and / or, The drying condition is that the temperature is 80-120℃ and the time is 6-12h; and / or, The calcination condition is that the temperature is increased to 500-600℃ at a temperature increasing rate of 1-2℃ / min, and the calcination time is 4-6h; preferably, the calcination is performed at 550-580℃. The full-silica molecular sieve obtained in the step (1) has a multi-level pore structure distribution, and is at least one of MFI type full-silica molecular sieve and MEL type full-silica molecular sieve; 8. The preparation method according to claim 5, characterized in that, Preferably, the particle size of the full-silica molecular sieve is 50-600nm; and / or, In the step (2), the molar ratio of the full-silica molecular sieve, the second auxiliary metal compound and water is 1: (0.1-1.0): (10-100), preferably 1: (0.1-0.5): (10-80), wherein the full-silica molecular sieve is calculated based on SiO2 contained therein; and / or, Preferably, the outer specific surface area of the all-silica molecular sieve is from 150 to 450 m 2 / g, preferably from 300 to 420 m 2 / g; and / or, Preferably, the mesopore volume of the all-silica molecular sieve is 0.5 to 1.5 cm3 / g, preferably 0.8 to 1.2 cm3 / g. 3 Preferably, the mesopore volume of the all-silica molecular sieve is 0.5 to 1.5 cm3 / g, preferably 0.8 to 1.2 cm3 / g. 3 Preferably, the mesopore volume of 9. The preparation method according to claim 5, characterized in that, The impregnation condition is that the temperature is 20-60℃ and the time is 4-12h; and / or, The solvent removal is performed by rotary evaporation, preferably, the rotary evaporation condition is that the temperature is 70-80℃, the rotation speed is 120-150rpm, and the vacuum degree is 65-75mbar; and / or, The drying condition is that the temperature is 80-120℃ and the time is 6-12h; and / or, The calcination condition is that the temperature is increased to 500-600℃ at a temperature increasing rate of 1-2℃ / min, and the calcination time is 4-6h; preferably, the calcination is performed at 550-580℃.
10. The low-noble metal content supported catalyst of any one of claims 1-3 or prepared by the method of any one of claims 4-9, for use in the dehydrogenation of propane, preferably for use in the production of propylene by dehydrogenation of propane.
11. The use according to claim 10, wherein the use comprises contacting propane with the low-noble metal content supported catalyst to produce propylene by dehydrogenation of propane in the presence of hydrogen. Preferably, in the dehydrogenation reaction, the propane gas mass space velocity is 1-50 h -1 -1, and / or the H2 / propane feed pressure ratio is 1:(1-8), and / or the dehydrogenation reaction temperature is 550-620°C.